ChemInform Abstract: Multivariate Statistical Analysis Methods in QSAR. Issue 9 (February 2016) - Pirhadi, Somayeh; Shiri, Fereshteh; Ghasemi, Jahan B.
Abstract: Review: QSAR: quantitative structure—activity relationship; 222 refs.